Review of the congrid eel genus Conger (Anguilliformes: Congridae) in Taiwan - Smith, David G.; Ho, Hsuan-Ching (Zootaxa, 2018)
The congrid eel genus Conger in Taiwan is reviewed. Five species are recognized, including C. jordani, C. cinereus, C. macrocephalus, C. myriaster and a newly collected species, C. philippinus. A mature male specimen of Conger myriaster is described for the first time. Specimens previously identified as C. japonicus (= C. myriaster) were misidentifications of above mentioned species. The diagnostic characters are discussed. Detailed data on all five species and a key to species in Taiwan are provided.